Pelaksanaan Program Intervensi Psikososial melalui Pemberdayaan Masyarakat terhadap Peningkatan Pengetahuan dan Keterampilan dalam Penanganan Masalah Psikososial di Kecamatan Bale Endah-Jawa Barat: Pelaksanaan Program Intervensi Psikososial melalui Pemberdayaan Masyarakat terhadap Peningkatan Pengetahuan dan Keterampilan dalam Penanganan Masalah Psikososial di Kecamatan Bale Endah-Jawa Barat - Yeni Hendriani; Desmaniarti Desmaniarti; Nani Avianti (Poltekkes Kemenkes Bandung, 2009)
Mental wellness is one of the important aspects in social life especially in Indonesia since there are many calamities that can influence the mental welness of the society. The situation in the area of calamities is considered not condusive for the people to struggle and they have high risk to some health problems. Community empowerment is one of strategy to help people in struggling to face the situation. The study aim is to find out the influence of psychosocial intervention through community empowerment on the knowledge and skill in tackling and preventing psychosocial problems post traumatic condition.The study use quasi experiment design with pre and post test and has been done in flood area in Andir and Bale Endah Districs. The intervention has been done within 3 weeks. The result of the study revealed that the intervention program can increase the knowledge and skill in tackling the calamities significantly (p=0,000) before and after intervention in both groups. Therefore, the intervention module can be used as a tool in helping the community in facing the mental disorder and other psychosocial problems.